Application Of The Inquiry Learning Model To Increase IPS Learning Outcomes In Class VIII Students Of Junior High School 9 Kendari - Hamsir Hamsir (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This study aims to improve social studies learning outcomes on interaction materials between countries in the ASEAN region in class VIII SMPN 9 Kendari through the application of the inquiry learning model. This research was conducted at SMPN 9 Kendari in the odd semester of the 2019/2020 academic year for 21 students in class VIII. Factors observed in this study were student factors and teacher factors. This research was carried out in 2 (two) cycles, including: a) planning; b) implementation of actions; c) observation and evaluation, d) reflection. The data obtained in this study were analyzed using descriptive statistics. The results showed that (1) the application of the guided discovery learning model could improve student learning outcomes with an average of 78.09 and a percentage of student learning completeness of 90.47%; (2) The application of the inquiry learning model can streamline the use of time and the presentation of information on the material of spatial interaction in life in ASEAN Countries; (3) The application of the inquiry learning model is a learning that conditions students to study in groups to complete tasks in turns until all students in their respective groups understand the material being studied and (4) the learning activities of students and teachers by applying the inquiry learning model to the material of spatial interaction In life in ASEAN Countries, the average student and teacher activity is 3.8 with good implementation criteria..